Designing a Women’s Participation Model to Support a Drug-Free Indonesia - Elnino M. Husein Mohi; Rukiah Nggilu; Misbahudin Djaba; Regi Mokodongan (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study aims to develop a model for women's participation in supporting Drug-Free Indonesia (Bersinar), incorporating an intersectional approach and gender-responsive policies. Given the complexity and multidimensional nature of the drug problem, this study positions women not merely as policy objects but as social actors with a crucial role in prevention, eradication, and rehabilitation. The research employed a qualitative approach grounded in library research, supported by field interviews with the Gorontalo National Narcotics Agency (BNNP) and local women's communities. The results indicate that women's participation remains symbolic, with limited involvement in social activities and in implementing the P4GN program, and no strategic role in policy formulation. This research yields a conceptual model of women's participation with three transformative stages: awareness, empowerment, and governance. This model is rooted in the Ladder of Citizen Participation theory, the Gender-Responsive Policy Framework, and Intersectional Feminism. This model offers a new direction for narcotics policy in Indonesia that is more inclusive, participatory, and humanistic, by positioning women as subjects of social change and strategic partners of the state in realizing a “Indonesia Bersinar.”